Development of an Agrobacterium‐delivered CRISPR/Cas9 system for wheat genome editing. Issue 8 (12th March 2019) - Zhang, Zhengzhi; Hua, Lei; Gupta, Ajay; Tricoli, David; Edwards, Keith J.; Yang, Bing; Li, Wanlong
Summary: CRISPR/Cas9 has been widely used for genome editing in many organisms, including important crops like wheat. Despite the tractability in designing CRISPR/Cas9, efficacy in the application of this powerful genome editing tool also depends on DNA delivery methods. In wheat, the biolistics based transformation is the most used method for delivery of the CRISPR/Cas9 complex. Due to the high frequency of gene silencing associated with co‐transferred plasmid backbone and low edit rate in wheat, a large T0 transgenic plant population are required for recovery of desired mutations, which poses a bottleneck for many genome editing projects. Here, we report an Agrobacterium ‐delivered CRISPR/Cas9 system in wheat, which includes a wheat codon optimized Cas9 driven by a maize ubiquitin gene promoter and a guide RNA cassette driven by wheat U6 promoters in a single binary vector. Using this CRISPR/Cas9 system, we have developed 68 edit mutants for four grain‐regulatory genes, TaCKX2‐1, TaGLW7, TaGW2, and TaGW8, in T0, T1, and T2 generation plants at an average edit rate of 10% without detecting off‐target mutations in the most Cas9‐active plants. Homozygous mutations can be recovered from a large population in a single generation. Different from most plant species, deletions over 10 bp are the dominant mutation types in wheat. Plants homozygous of 1160‐bp deletion in TaCKX2‐D1 significantly increased grain number per spikelet. In conclusion, our Agrobacterium ‐delivered CRISPR/Cas9 system provides an alternative option for wheat genome editing, which requires a small number of transformation events because CRISPR/Cas9 remains active for novel mutations through generations.